Review of imaging technologies used in Hidradenitis Suppurativa. Issue 1 (8th October 2019) - Elkin, Kenneth; Daveluy, Steven; Avanaki, Kamran
Abstract: Background: Until recently, clinical assessment with manual palpation of the HS lesions was the primary means to detect HS lesions and their borders. In the past decade, there has been increased application of imaging technologies to HS patients, and it is reported that manual palpation consistently underestimates HS. Of the technologies, ultrasound (US) imaging has been the most efficacious and well‐studied. In the present review, we will discuss the various imaging modalities that aid in detecting, managing, and treating HS. Materials and Methods: Non‐invasive HS imaging technologies including ultrasound (US) imaging, magnetic resonance imaging (MRI), medical infrared thermography (MIT), positron emission topography (PET), and computed tomography (CT) were reviewed and compared through a review of the literature. PubMed, Google, and Google Scholar were utilized. Results: Of the 4 HS technologies reviewed, US imaging and MRI are the most established and useful non‐invasive modalities utilized in HS patients. However, MIT may have potential to aid in the pre‐operative and intra‐operative surgical excision of HS lesions. Conclusion: For imaging HS lesions, US imaging is the most well‐characterized and has the greatest range of use, while MRI has a role in severe, anogenital HS lesions. MIT of HS lesions is a novel application and merits attention.